Theoretical Foundations for Entrepreneurship Development Program - Silwal, Yam Bahadur; Poudel, Saroj Kumar; Dahal, Keshav Prasad; Thapaliya, Shekhar; Sah, Barun Kumar (Nepal Journal of Multidisciplinary Research, 2022)
Entrepreneurship development is a process of converting an ordinary individual into an entrepreneur. The objective of this study is to examine theories of entrepreneurship development in order to gain a deeper understanding of the development of entrepreneurship. There are a number of entrepreneurship development theories existed in the scholarly field. The study identifies that entrepreneurship development theories are contextual and may not be applicable in all contexts. Some of the theories focus on psychological and knowledge aspects whereas some of them focus on skills, social network, institutional arrangement and support. A single theory has been found to be insufficient for the overall development of entrepreneurship. This study has included that mainly four theories: human capital theory of entrepreneurship development, institutional theory of entrepreneurship development, innovation theory of entrepreneurship development and social capital theory of entrepreneurship development This consolidated form of four theories provides the knowledge, skills, abilities, and practices necessary for an individual to be prepared for entrepreneurship. Findings of this study will provide insights for those government, non-government and private institutions that are involved in the entrepreneurship development programs.